Ethical Leadership in Community Colleges: Navigating Challenges through the Lenses of Justice, Critique, Care, and Local Community - Greg Peterson; Sandy L. Robinson; Larry Rideaux Jr. (Educational Considerations, 2025)
Community colleges face many challenges post-pandemic in fulfilling their open-access mission while weathering increasing complexities, resource limitations, and overall declining confidence in higher education. Ethical leadership is required for community college leaders seeking to successfully address these challenges. Ethical leadership paradigms can be valuable tools in helping leaders understand their values and the implications these values have on the decisions they make. This article uses Wood and Nevarez’s (2014) four-paradigm framework of the Ethic of Justice, Ethic of Critique, Ethic of Care, and Ethic of Local Community to explore ethical paradigms and their application within the community college leadership setting. The authors argue that the use of all four ethical paradigms best positions a community college leader to successfully weather current and future challenges higher education will face.
Keywords: Community Colleges; Ethical Leadership; Ethical Paradigms; Community College Leaders